Words of empowerment: (pseudo-)scientific discourse in magazine advertisements - Simões, Elsa; Tuna, Sandra (Redis: Revista de Estudos do Discurso, 2017)
It is the purpose of this essay to undertake a reflection on the different strategies used in magazine advertisements in order to acquire discursive credibility, which is something advertising discourse, in general, is normally denied. After a theoretical incursion on the practice of discourse borrowing in advertising, we will concentrate on the analysis of advertising strategies which draw on (a) medicine and medical speech, (b) mathematics and mathematical jargon, and (c) environmentally-friendly discourse to enhance and substantiate their claims. In order to analyze these three different strategic options, we will be focusing on a corpus constituted by magazine ads. Although we are using a limited corpus for the present work, it would be possible to point out, in a tentative manner, to the existence of an increasing trend towards the use of science (and scientifically-grounded arguments) to confer further credibility to ads, something which can also be advantageously used as differentiation factor in a highly cluttered market, even if, very often, what is being used is merely a mimicking of the most easily recognizable discursive characteristics of such discourse, and not scientific discourse in toto.